2017
DOI: 10.1007/s00441-017-2681-1
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural features of aberrant glial cells isolated from the spinal cord of paralytic rats expressing the amyotrophic lateral sclerosis-linked SOD1G93A mutation

Abstract: In the rat model of amyotrophic lateral sclerosis expressing the G93A superoxide dismutase-1 mutation, motor neuron death and rapid paralysis progression are associated with the emergence of a population of aberrant glial cells (AbAs) that proliferate in the degenerating spinal cord. Targeting of AbAs with anti-neoplasic drugs reduced paralysis progression, suggesting a pathogenic potential contribution of these cells accelerating paralysis progression. In the present study, analyze the cellular and ultrastruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
61
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(68 citation statements)
references
References 51 publications
7
61
0
Order By: Relevance
“…Previous morphological studies on AbGC with MitoTracker Green evidenced that mitochondria appear clustered in the perinuclear area and that their main axis was shorter than that observed in neonatal nTg astrocytes as assessed in transmission electron microscopy (TEM) images [21]. Our measurements of mitochondrial length in MitoTracker Green-stained AbGC and nTg neonatal astrocytes were in the range of these previous TEM quantitative data.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Previous morphological studies on AbGC with MitoTracker Green evidenced that mitochondria appear clustered in the perinuclear area and that their main axis was shorter than that observed in neonatal nTg astrocytes as assessed in transmission electron microscopy (TEM) images [21]. Our measurements of mitochondrial length in MitoTracker Green-stained AbGC and nTg neonatal astrocytes were in the range of these previous TEM quantitative data.…”
Section: Discussionsupporting
confidence: 76%
“…AbGC simultaneously express astrocytic glial fibrillary acidic protein (GFAP), S100β, and Connexin-43 (Cx-43) [19] and microglial Iba-1, CD11b, and CD163 markers [20], at least at initial stages of culture. Furthermore, they exhibit features of cellular stress and inflammatory activation [21], a highly proliferative phenotype [19], and induce extensive gliosis after focal transplantation into the spinal cord of nTg rats [22]. Thus, detailed characterization of their toxic phenotype may contribute to understanding pathogenic mechanisms and therapeutic development in ALS.…”
Section: Introductionmentioning
confidence: 99%
“…Further evidence for the aberrant nature of cultured aberrant glial cells isolated from SOD1 G93A symptomatic rats has been obtained from ultrastructural analysis . Cells show an absence of intermediate filaments, an abundance of microtubules together with an important production of extracellular matrix components, suggesting a pro‐fibrotic activity.…”
Section: From Activated Glial Cells To the Emergence Of Aberrant Phenmentioning
confidence: 99%
“…Further evidence for the aberrant nature of cultured aberrant glial cells isolated from SOD1 G93A symptomatic rats has been obtained from ultrastructural analysis. 67 Cells show an absence of intermediate filaments, an abundance of microtubules together with an important production of extracellular matrix components, suggesting a pro-fibrotic activity. In addition, cells showed exacerbated endoplasmic reticulum stress together with a significant abundance of lipid droplets, autophagy images and many heterogeneous formations including vesicles, suggesting a role in secretion.…”
Section: Ultrastructural Features Of Aberrant Glial Cellsmentioning
confidence: 99%
“…described previously(Jiménez-Riani et al, 2017), and ultrathin sections were observed with a Jeol JEM1010 transmission electron microscope.3 | RESULTS3.1 | Effect of a coverslip hypoxia variant on LNCaP cell morphology, hypoxic state, and extracellular pHWe modified previous versions of the coverslip hypoxia method by culturing cells in the wells of 35-mm glass bottom dishes and sealing the wells with coverslips larger than the diameter of the well. The coverslips…”
mentioning
confidence: 99%